Primary segmental volvulus of the ileum in a fetus: Case report - Younglim Kim; Jongyun Hwang; Suk-Bae Moon (Elsevier, 2015)
Primary intestinal volvulus in a fetus without an underlying cause has been rarely reported. We report a case of fetal primary segmental volvulus of the ileum. A 27-year-old woman was referred at 32 weeks of gestation for evaluation of decreased fetal movement. A fetal ultrasound detected a single, significantly-dilated bowel loop without a vascular supply (coffee bean sign), and a fetal MRI revealed the 'whirl-pool sign'. An emergency cesarean delivery and laparotomy revealed segmental volvulus of the ileum without any causative factors. Segmental resection resolved the condition without sequelae. Fetal primary segmental volvulus can occur without any underlying pathology, and rapid diagnosis and prompt intervention is mandatory for a good outcome.